2021
DOI: 10.3390/biom11091272
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases as Biomarkers and Treatment Targets in Mesothelioma: A Systematic Review

Abstract: Metalloproteinases (MMPs) have an important role in tissue remodeling and have been shown to have an effect on tumor progression, invasion, metastasis formation, and apoptosis in several tumors, including mesothelioma. Mesothelioma is a rare tumor arising from pleura and peritoneum and is frequently associated with asbestos exposure. We have performed a systematic search of PubMed.gov and ClinicalTrials.gov databases to retrieve and review three groups of studies: studies of MMPs expression in tumor tissue or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Metalloproteinases are strongly implicated in most of the dysregulated processes in cancer, such as tumor growth, metastasis and angiogenesis and are highly expressed in mesothelioma, particularly MMP2 and MMP9 [ 63 ]. In agreement with our previous in vitro findings in PM cells [ 29 ], we show here that the in vivo treatment with MIA-690 inhibited the mRNA expression of both MMP2 and MMP9 in PM tumors, an effect elevated by the combination of MIA-690 with cisplatin/pemetrexed, compared with chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Metalloproteinases are strongly implicated in most of the dysregulated processes in cancer, such as tumor growth, metastasis and angiogenesis and are highly expressed in mesothelioma, particularly MMP2 and MMP9 [ 63 ]. In agreement with our previous in vitro findings in PM cells [ 29 ], we show here that the in vivo treatment with MIA-690 inhibited the mRNA expression of both MMP2 and MMP9 in PM tumors, an effect elevated by the combination of MIA-690 with cisplatin/pemetrexed, compared with chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…A potential gene–environment interaction between MMP SNPs and asbestos, which is the major risk factor for MMP, has been previously shown, with certain genetic variants in MMP genes exerting either protective or tumor-promoting effects on mesothelioma development [ 64 ]: (i) an Italian-based GWAS study found that MMP14 , among other genes, could be a risk factor for MPM [ 25 ] and (ii) MMP2 rs243865 polymorphism has been described as protective for pleural mesothelioma development [ 65 ]. R-HSA-1474228 disruption in MPM individuals is a further confirmation that MMP polymorphisms influence the risk of mesothelioma.…”
Section: Discussionmentioning
confidence: 99%
“…The review by Mougin et al [ 9 ] focused on what is known about the ADAMTS family involved in human aneurysms from human tissues to mouse models, and they also discussed the possibility to develop, in the future, specific therapeutic approaches using inhibitors targeting the ADAMTS. Štrbac et al [ 10 ] systematically reviewed findings on the role of MMPs as potential biomarkers and treatment targets in mesothelioma, and they found that the need for new therapeutic approaches in mesothelioma is great, and that MMPs may be interesting, not only as biomarkers, but also as treatment targets. Andreucci M et al [ 11 ] explored the role MPs in the development of aortic aneurysms, their link with chronic kidney disease, and the mechanisms by which each of these conditions impairs the prognosis of the other.…”
mentioning
confidence: 99%